Telomerase – molecular marker in blood of ovarian cancer patients - Góra, Ewa; Korczyński, Jerzy; Wójcik-Krowiranda, Katarzyna; Gottwald, Leszek; Bieńkiewicz, Andrzej (Menopause Review/Przegląd Menopauzalny, 2009)
Studies conducted in last 10 years suggest diagnostic and prognostic significance of circulating tumour cells (CTC) detection using expression of molecular markers detected in Real-Time PCR (RT-PCR). Telomerase is one of this markers as a potential and prognostic factor for several cancers including ovarian cancer. Objectives: The aim of the study was to estimate telomerase as molecular marker for ovarian cancer and to establish its diagnostic and prognostic importance. The study was performed in Department of Oncologic Gynaecology of Medical University of Lodz and Department of Molecular Cancerogenesis of Medical University of Lodz. Materials and methods: There were 57 patients included who were diagnosed ovarian tumour, without previous treatment. Control group consisted of 20 healthy women. From each patient blood was collected and after isolation of CTCs using immunomagnetic beads and density gradient centrifugation mRNA was isolated. Then, there was an expression of TERT detected by RT-PCR and confirmed in electrophoresis. Correlations between expression of gene analysed in study and prognostic factors for ovarian cancer were measured. Results were submitted statistical analysis. Results: A positive expression of TERT (simultaneously in RT-PCR and electrophoresis) was reported in 14 out of 33 patients (42,4%) in the group with malignant tumours, 5/24 (20,8%) in women from the group II and 7/20 (35%) from the control group. There was no significant difference between expression of TERT using different methods in each group and between groups. There was neither no significant relationship between expression of this gene and prognostic factors of ovarian cancer. Conclusions: Telomerase can’t be used as sufficiently sensitive and specific molecular marker for CTCs detection in blood in ovarian cancer patients using presented method.